CVPR 2011 2011
DOI: 10.1109/cvpr.2011.5995415
|View full text |Cite
|
Sign up to set email alerts
|

From co-saliency to co-segmentation: An efficient and fully unsupervised energy minimization model

Abstract: We address two key issues of co-segmentation over multiple images. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
164
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(164 citation statements)
references
References 30 publications
(54 reference statements)
0
164
0
Order By: Relevance
“…The saliency factor estimated for regions is fairly benefit for object co-segmentation [16], classification [17], retrieval [18] and object tracking [19]. A solution of color transfer by the mean and variance of colors [1] is enforced with saliency map in [20].…”
Section: Prior Workmentioning
confidence: 99%
“…The saliency factor estimated for regions is fairly benefit for object co-segmentation [16], classification [17], retrieval [18] and object tracking [19]. A solution of color transfer by the mean and variance of colors [1] is enforced with saliency map in [20].…”
Section: Prior Workmentioning
confidence: 99%
“…These methods aim at salient region extraction for individual images, while ignoring useful global information available from correlated image collections. Recently, co-saliency methods have been proposed to find common salient object(s) between pair of images [10,39] or among multiple images [8,52]. Such methods, however, require salient areas to contain parts of the foreground objects across most images.…”
Section: Related Workmentioning
confidence: 99%
“…We found that considering the largest appearance cluster [3] or top-ranked internet images [25] as an initial set to be unsatisfactory. In an interesting effort, Chang et al [8] use repeatedness among images as a global prior of multiple images and assume that most images contain at least parts of the foreground object, an assumption that is often violated in our setting. Further, since each image is compared with all others, the method cannot be used for large collections (e.g., they considered image sets of maximum size 30, while we handle a few 1000 s).…”
Section: Statistical Global Appearance Modelsmentioning
confidence: 99%
“…Considering the inter-image correspondence, researchers recently improve the saliency model in single image and propose the co-saliency model for multiple images [5,14,15]. Saliency and co-saliency models have been used in some co-segmentation methods [5,7,13].…”
Section: Intra-image Energy Termmentioning
confidence: 99%
“…Hochbaum and Singh [3] modify the global energy term using similarity between foreground histograms and then apply a max-flow solution like Graph Cuts [4] to efficiently optimize the energy function. Chang et al [5] formulate the global energy term by simultaneously considering foreground dissimilarity and dissimilarity between foreground and background. Rubio et al…”
Section: Introductionmentioning
confidence: 99%